Conversational Implicature in the Film Nanti Kita Cerita tentang Hari Ini: A Pragmatic Analysis - Rahmawan, Muh Reva Fitra (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
This study aims to identify the implicatures present in dialogues among characters in the film Nanti Kita Cerita tentang Hari Ini. The data source of this research consists of character dialogues in the film that reflect conversational implicatures. The focus of the study is to identify implicatures contained in the characters’ utterances. Data were collected using observation and note-taking techniques. The implicatures identified include conversational implicatures and conventional implicatures. One of the main functions of implicature is to soften utterances, making them more polite. The film Nanti Kita Cerita tentang Hari Ini demonstrates various types of implicature, such as those expressing emotions, beliefs, and rejection. This indicates that dialogues which do not adhere to the cooperative principle may generate certain implicatures in conversation. The findings reveal that implicatures in the film function not only as linguistic devices but also as emotional strategies within family relationships. The characters employ implicature to convey disappointment, affection, and inner conflict without expressing them explicitly.